Boron Nitride Monolayers: Charge State Control of F16CoPc on h‐BN/Cu(111) (Adv. Mater. Interfaces 15/2020). Issue 15 (6th August 2020) - Pörtner, Mathias; Wei, Yinying; Riss, Alexander; Seufert, Knud; Garnica, Manuela; Barth, Johannes V.; Seitsonen, Ari P.; Diekhöner, Lars; Auwärter, Willi
Abstract : The image visualizes three parameters used to control the electronic structure of adsorbed metal‐organic complexes, namely the nanostructured hexagonal boron nitride support, the tip of a scanning probe microscope, and the molecular environment. The templating functionality of the atomically thin hexagonal boron nitride layer is highlighted by the array of individual fluorinated Co‐phthalocyanine molecules in the background. The tip (top right) gates and probes the molecule's electronic structure, which can be tuned by the molecular arrangement. This effect is indicated by the green and red density‐functional‐theory‐derived density contours of the molecular trimer in the foreground, where the electronic structure of the central molecule (in red) differs from the one of the outer molecules (in green). In addition, an insight into the chemical structure of the metal‐organic complexes is provided. More details can be found in article number 2000080 by Yinying Wei, Willi Auwärter, and co‐workers.